A new specimen of the sauropodomorph dinosaur Ignavusaurus rachelis from the Early Jurassic of Lesotho - Bodenham, Ewan H; Barrett, Paul M (Evolutionary Studies Institute, 2020)
The upper Elliot Formation (?Rhaetian–Sinemurian) of South Africa and Lesotho has yielded a rich fauna of non-avian dinosaurs, which has generally been considered to be dominated by the massopodan sauropodomorph Massospondylus carinatus. However, re-evaluation of the abundant sauropodomorph collections from this unit suggests that the species-richness of upper Elliot sites has been underestimated. Here, we describe a series of cervical and dorsal vertebrae collected from Likhoele Mountain, Lesotho, which are referred to the rare upper Elliot sauropodomorph taxon Ignavusaurus rachelis. This material represents only the second-known specimen of this taxon, extending its geographic range, and underscores the value of undertaking detailed re-assessments of neglected historical collections.
Keywords: sauropodomorpha; massospondylidae; upper Elliot Formation; taxonomy